Modeling the Process of Obtaining Liquid Pyrolysis Products of Plant Biomass Taking into Account the Rate of their Cooling - S. V. Vasilevich; M. V. Malko; D. V. Degterov; A. N. Asadchy (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article presents the results of computational and experimental studies of thermochemical conversion of wood biomass to obtain liquid pyrolysis products taking into account their cooling rate. The method of calculating the optimal operating parameters (temperature and cooling rate) of the techno-logical process is presented. An expression is proposed to determine the consumption of wood raw materials depending on the temperature of the thermochemical conversion process. It is noted that the mass yield of liquid pyrolysis products from the reactor poorly depends on temperature and is approximately 0.45 in the range from 573 to 923 K. To assess the effect of the cooling rate of liquid pyrolysis products, a third-order differential equation was used for a model limited by the reaction rate. It has been shown that when liquid pyrolysis products are cooled, the degree of their conversion tends to a certain value other than 1 (depending on the cooling rate). Calculated data on the dependence of the degrees of conversion of liquid wood pyrolysis products on time at different cooling rates and temperatures of thermochemical conversion of biomass have been obtained. It has been established also that the ratio of the mass yield of cooled liquid pyrolysis products to the initial loading of the pyrolysis reactor makes it possible to find optimal cooling conditions for the primary products of biomass pyrolysis carried out at certain temperatures. Graphs of the dependence of this parameter on the temperature of the thermochemical conversion of wood biomass for different cooling rates of liquid pyrolysis products are presented. It is shown that the maximum possible yield of liquid products is provided at a reactor temperature of 923–973 K and a cooling rate of 700000–1200000 degrees/min. However, achieving such cooling rates is rather a difficult technical task. Therefore, more limited temperature 773–800 K is accepted, at which a practically realizable cooling rate of primary biomass de-composition products is achieved.